2023
DOI: 10.1101/2023.01.09.523296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Growth substrate limitation enhances anaerobic arsenic methylation byParaclostridium bifermentansstrain EML

Abstract: Microbial arsenic (As) methylation is established as a detoxification process under aerobic conditions (converting arsenite) to monomethylarsonic acid (MMAs(V))) but proposed to be a microbial warfare strategy under anoxic conditions due to the toxicity of its main product monomethylarsonous acid (MMAs(III)). Here, we leveraged a recently isolated anaerobic As methylator, Paraclostridium bifermentans strain EML to gain insights into this process. Strain EML was inoculated into a series of media that consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
(154 reference statements)
0
0
0
Order By: Relevance
“…While production of DMA and TMAO was roughly two and 4-fold greater in the 100% strength R2A compared to the 10% strength R2A, respectively, the more than 6-fold increase in OD 600 from 10% to 100% strength R2A led to a sharp decrease in biomass-normalized methylation efficiencies (Figure S11). This result is similar to recent findings in Qiao et al, where biomass-normalized arsenic methylation by Paraclostridium bifermentans strain EML was inhibited at higher media concentrations.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While production of DMA and TMAO was roughly two and 4-fold greater in the 100% strength R2A compared to the 10% strength R2A, respectively, the more than 6-fold increase in OD 600 from 10% to 100% strength R2A led to a sharp decrease in biomass-normalized methylation efficiencies (Figure S11). This result is similar to recent findings in Qiao et al, where biomass-normalized arsenic methylation by Paraclostridium bifermentans strain EML was inhibited at higher media concentrations.…”
Section: Resultssupporting
confidence: 92%
“…To our knowledge this is the first report to link carbon source quantity and quality to the control of As methylation through a CCR-like mechanism, but a close examination of recent studies reveals findings that are consistent with this theory. For example, Qiao et al showed that biomass-normalized As methylation by P. bifermentans decreased with higher media carbon concentrations, while Leon Ninin et al reported a plateau followed by a decrease in methylated As in paddy soil incubations as DOC concentrations increased. We acknowledge that the literature generally suggests that organic matter stimulates As methylation, ,, but these prior observations may be caused by enhanced biomass growth in carbon-rich systems that obscures the repression of methylation on a per-cell basis.…”
Section: Resultsmentioning
confidence: 99%